Analysis of the Stability of α→γ Plane Front of Recrystallization in Ferritic Alloys During Carburization - Movchan, O.V.; Chernoivanenko, K.O. (Металлофизика и новейшие технологии, 2019)
The α → γ recrystallization of carbon-supersaturated ferrite alloyed with α-stabilizer is analysed. The α-stabilizer is redistributed between austenite and ferrite by recrystallization. A plane front of recrystallization becomes unstable and is transformed into cellular or dendrite one. The perturbation method, which is developed by W. W. Mullins and R. F. Sekerka for crystallizing alloys, is used in the analysis. Проанализирована α → γ-перекристаллизация при пересыщении углеродом феррита, легированного α-стабилизатором. При перекристаллизации α-стабилизатор перераспределяется между аустенитом и ферритом, плоский фронт перекристаллизации теряет устойчивость и трансформируется в ячеистый или дендритный. При анализе был использован метод возмущений, который был разработан W. W. Mullins, R. F. Sekerka для кристаллизующихся сплавов. Проаналізовано α → γ-перекристалізацію при пересиченні Карбоном фериту, леґованого α-стабілізатором. При перекристалізації α-стабілізатор перерозподіляється між аустенітом і феритом, плаский фронт перекристалізації втрачає стійкість і трансформується в комірчастий або дендритний. При аналізі було використано методу збурень, яку було розроблено W. W. Mullins, R. F. Sekerka для стопів, що кристалізуються.